ANALISIS DAMPAK BULLYING TERHADAP KEPERCAYAAN DIRI REMAJA - Pramanik, Gina Furi; Rohman, Ujang; Ismail, Shalahudin (Realita : Jurnal Bimbingan dan Konseling, 2024)
Bullying is a social phenomenon that can have a serious impact on adolescent development, one of which is the aspect of self-confidence. This research aims to analyze the impact of bullying on adolescent self-confidence. The research method used is a literature review of various studies and research that have been carried out regarding this topic. The results of the analysis show that teenagers who are victims of bullying tend to experience a decrease in self-confidence. Various forms of bullying, such as verbal, physical, relational and cyber bullying, have a significant impact on the psychological aspects of adolescents. Adolescents who are victims of bullying often experience feelings of fear, low self-esteem, difficulty interacting socially, and difficulty developing their own identity.